Localization of Epigenetic Markers in Leishmania Chromatin - Jacquelyn R. McDonald; Bryan C. Jensen; Aakash Sur; Iris L. K. Wong; Stephen M. Beverley; Peter J. Myler (Pathogens, 2022)
Eukaryotes use histone variants and post-translation modifications (PTMs), as well as DNA base modifications, to regulate DNA replication/repair, chromosome condensation, and gene expression. Despite the unusual organization of their protein-coding genes into large polycistronic transcription units (PTUs), trypanosomatid parasites also employ a “histone code” to control these processes, but the details of this epigenetic code are poorly understood. Here, we present the results of experiments designed to elucidate the distribution of histone variants and PTMs over the chromatin landscape of Leishmania tarentolae. These experiments show that two histone variants (H2A.Z and H2B.V) and three histone H3 PTMs (H3K4me3, H3K16ac, and H3K76me3) are enriched at transcription start sites (TSSs); while a histone variant (H3.V) and the trypanosomatid-specific hyper-modified DNA base J are located at transcription termination sites (TTSs). Reduced nucleosome density was observed at all TTSs and TSSs for RNA genes transcribed by RNA polymerases I (RNAPI) or RNAPIII; as well as (to a lesser extent) at TSSs for the PTUs transcribed by RNAPII. Several PTMs (H3K4me3, H3K16ac H3K20me2 and H3K36me3) and base J were enriched at centromeres, while H3K50ac was specifically associated with the periphery of these centromeric sequences. These findings significantly expand our knowledge of the epigenetic markers associated with transcription, DNA replication and/or chromosome segregation in these early diverging eukaryotes and will hopefully lay the groundwork for future studies to elucidate how they control these fundamental processes.